Pathological characteristics of low risk prostate cancer based on totally embedded prostatectomy specimens. Issue 4 (21st November 2014) - Swanson, Gregory P.; Epstein, Jonathan I.; Ha, Chul S.; Kryvenko, Oleksandr N.
<x xml:space="preserve">Abstract</x> Background Surveillance and focal therapy are increasingly considered for low risk prostate cancer (PC). We describe pathological characteristics of low risk PC at radical prostatectomy in contemporary patients. Methods Five‐hundred‐fifty‐two men from 2008 to 2012 with low risk (stage T1c/T2a, PSA ≤ 10 ng/ml, Gleason score ≤6) PC underwent radical prostatectomy. Slides were re‐reviewed to grade and stage the tumor, map separate tumor nodules, and calculate their volumes. Results Ninety‐three (16.9%) men had prostatectomy Gleason score 3 + 4 = 7 or higher and were excluded. Five (0.9%) men had no residual carcinoma. Remaining 454 patients composed the study cohort. The median age was 57 years (36–73) and median PSA 4.4 ng/ml (0.4–9.9). Racial distribution was 77.5% Caucasian, 15.5% African American, and 7% other. The median total tumor volume was 0.38 cm3 (0.003–7.22). Seventy percent of the patients had bilateral tumor and 34% had a tumor nodule >0.5 cm3. The index lesion represented 89% (median) of the total tumor volume. Extraprostatic extension and positive margin were present in 5.7% and 9% of cases, respectively. The tumor nodules measuring >0.5 cm3 were located almost equally between the anterior (53%) and peripheral (47%) gland. The relationship between PSA and total tumor volume was weak (r = 0.13, P = 0.005). The relationship between PSA density and total tumor volume was slightly better (r = 0.26, P < 0.001). Conclusions Low risk prostate cancer is generally a low volume disease. Gleason score upgrade is seen in 16.9% of cases at radical prostatectomy. While the index lesion accounts for the bulk of the disease, the cancer is usually multifocal and bilateral. Neither PSA nor PSA density correlates well with the total tumor volume. Prostate size has a significant contribution to PSA level. These factors need to be considered in treatment planning for low risk prostate cancer. Prostate 75:424–429, 2015. © 2014 Wiley Periodicals, Inc.